Strategi Pemasaran Dalam Rangka Meningkatkan Penjualan Keramik Private Label Dan Memenangkan Kompetisi Pada Pt.Catur Mitra Sejati Sentosa,Tbk (Mitra10) - Henry dan Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Recently, the development of building materials supermarket business is growing fast and rapidly, this can be seen from the rapid growth of the Indonesia’s economy. One of the building materials supermarket in Indonesia is Mitra10. Mitra10 has 27 stores spread across Indonesia but unfortunately Mitra10's sales still can’t catch up its competitor, Depo Bangunan. Depo Bangunan only has 8 stores in Indonesia so Mitra10 must analyze the internal, external and industrial environments related to building materials supermarket business then analyze it using CP Matrix. Depo Bangunan is considered as a market leader in building and materials field so Mitra10 must conduct an offensive strategy by using a frontal attack on price, people, rapid delivery and customer service by using a private label so that Mitra10's private label will be increasingly known and at the same time subsidize high profit margins and logistic costs. The use of this strategy is applied to segment A which is considered as a warzone in a place that intersect with Depo Bangunan, with an undifferentiated strategy and applying positioning on private label products that are divided based on high end class, middle class and low class. The implementation of STP is assisted by a marketing mix where the price given in the warzone area is a local brand price that is equated with the price at Depo Bangunan and the private label price is given lower than the local brand in the Depo Bangunan or Mitra10 then the product will follow motives in Depo Bangunan that sell quickly so that the assortment and variety of products will increase, the expansion of Mitra10 will be faster and at last, the convenience of consumers when shopping also have to be considered so that consumers will be more loyal to Mitra10.